A note on flag-transitive 3-(v, k, 2) designs - Dai, Shaojun; Gong, Luozhong; Li, Shangzhao (Utilitas Mathematica, 2019)
This article is a contribution to the study of the automorphism groups of 3-(v, k, 2) designs. Let S=(P,β) be a non-trivial 3-(q + 1, k, 2) design. If G acts flag-transitively on S} then G is not two-dimensional projective linear group PSL(2,q). © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.